STRATEGI PEMASARAN: UPAYA PT. PERUSAHAAN GAS NEGARA TBK AREA LAMPUNG DALAM MENINGKATKAN VOLUME PENJUALAN PELANGGAN RUMAH TANGGA - Sari, Murni; Pratama, Maulana Agung; Aprilia, Hani Damayanti (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2025)
This research aims to find out how PGN Lampung Area will implement its marketing plan to increase the sales volume of the natural gas network development program for household customers. This research uses qualitative techniques and is a descriptive research project. The data collection methods chosen in this research include interviews, observation, documentation and literature study. This research utilizes source triangulation techniques in data validity techniques and interactive data analysis techniques are used in data analysis. This research focuses on the 7P marketing mix which includes Product, Price, Place, Promotion, People, Process, and Physical Evidence. The STP approach is also the main emphasis of this research. Based on the research results, PGN Lampung Area uses marketing strategies, including providing high quality products at competitive prices with similar products, running promotional media, installing pipe networks in several potential locations, competent human resources in their fields, and having efficient service procedures. Has the advantage of complete facilities and infrastructure. The marketing strategy implemented by PGN Lampung Area was able to significantly increase the sales volume of the household gas network program, thereby adding value to the company's contribution to meeting the community's energy needs. This is made possible by the results of Segmenting, Targeting and Positioning (STP) analysis. Findings It is hoped that this research will serve as a guide for businesses wishing to improve the effectiveness of the marketing tactics they use to identify the best actions to increase sales volume and strengthen their position in the industry. Keywords : Marketing Strategy, Natural Gas, Sales Volume, Household Gas Networks.